Labour Markets in Libya: Opportunities and Risks - Any, Salih; Yildiz, Neşe (Journal of Pure & Applied Sciences, 2024)
The Libyan economy faces significant challenges due to its lack of diversification, with the public sector dominating the labour market. This dominance has led to high unemployment rates, job instability, skills shortages, and widespread informal employment. This research critically examines the current state of the Libyan labour market, identifying both opportunities and risks, and provides a comprehensive overview of Libya’s workforce. The analysis reveals that 67% of the Libyan population is under the age of 35, representing a substantial and expanding workforce. Libya’s strategic location in North Africa provides access to European and African markets, potentially fostering economic growth and job creation. However, a misalignment between workforce skills and private sector requirements impedes sustainable development. Additional challenges include a weak private sector, economic identity issues, and political instability. Reducing reliance on oil and gas, combating corruption, and enhancing the education system are essential for achieving economic resilience and social stability. The findings indicate that labour market programs and institutions have had minimal impact on outcomes, with notable disparities between capital owners and income earners. Women face significant barriers to economic empowerment, despite the presence of inclusive sectors such as hospitality and financial services. Barriers to inclusivity and productivity, including gender disparities, skills mismatches, education gaps, and issues within the informal labour market, persist. Policy interventions are crucial to capitalize on these opportunities and mitigate associated risks through comprehensive labour market strategies.